Path Guide: A New Approach to Indoor Navigation - Shu, Yuanchao; Karlsson, Börje F. (2017)
Mobile outdoor GPS navigation apps have proven to be lifesavers to countless people. With a smartphone in hand, it is easy to find your way to a destination, even in an unfamiliar city. However, it is still easy to get lost indoors, where GPS satellite signals are not accurately traceable for navigation applications. How often have you had a hard time locating that new café inside in a bustling shopping center where you were supposed to meet your friends? How often have you wandered the hallways of some office building trying desperately to find that meeting room you were supposed to be in? How convenient would it be to have an app, similar to the ones used outdoors, that works indoors? We at Microsoft Research Asia’s Cloud & Mobile Research group recently launched Path Guide, a research-based application that provides low-cost, plug-and-play indoor navigation services. Users can easily find the correct path to their destinations by simply following traces created by a “leader,” or user who has been to the location before.